Packets Wavelets and Stockwell Transform Analysis of Femoral Doppler Ultrasound Signals - M. Latfaoui; F. Bereksi Reguig (International Journal of Electrical and Computer Engineering (IJECE), 2018)
Ultrasonic Doppler signals are widely used in the detection of cardiovascular pathologies or the evaluation of the degree of stenosis in the femoral arteries. The presence of stenosis can be indicated by disturbing the blood flow in the femoral arteries, causing spectral broadening of the Doppler signal. To analyze these types of signals and determine stenosis index, a number of time-frequency methods have been developed, such as the short-time Fourier transform, the continuous wavelets transform, the wavelet packet transform, and the S-transform.